PENDAMPINGAN PELATIHAN WEB E COMMERCE SEBAGAI MEDIA PEMASARAN DI SMK DARUSSALAM GANDING SUMENEP - Tianah, Itaanis; Azizah, Siti; Abdullah, Fatikhul Amin; Rahman, Hadiatur; Khairi, Ahmad Imam; Romadhan, Sahrul (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Marketing product through digital network has been widely used in the last few decades. Today’s young generation must have additional skills to be able to adapt with the changing times and be able to become national or international entrepreneur. The object of this empowerment is SMK Islam Darussalam’s students. By using ABCD method that is identyfing the SMK Islam Darussalam’s asset obtained that they have Batik product, unfortunately the product still marketed at the local level. Through web e-commerce training, students have additional skills for selling their products